2017
DOI: 10.1111/apa.14015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and infant factors had a significant impact on birthweight and longitudinal growth in a South African birth cohort

Abstract: AimThis birth cohort study investigated longitudinal infant growth and associated factors in a multiethnic population living in a low‐resource district surrounding the town of Paarl in South Africa.MethodsBetween March 2012 and October 2014, all mothers attending their second trimester antenatal visit at Paarl Hospital were approached for enrolment. Mother–infant pairs were followed from birth until 12 months of age. Comprehensive socio‐demographic, nutritional and psychosocial data were collected at birth, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
4
34
0
2
Order By: Relevance
“…The authors therefore used a cutoff of birthweight £2500g. The prevalence of LBW in the sample of 13.64% is closely aligned with recent cohort studies of birthweight in South Africa (22,28).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The authors therefore used a cutoff of birthweight £2500g. The prevalence of LBW in the sample of 13.64% is closely aligned with recent cohort studies of birthweight in South Africa (22,28).…”
Section: Discussionsupporting
confidence: 82%
“…In addition to the primary exposure of the household food security score, we included variables associated with LBW and stunting in the literature in our models. These included both distal and proximate characteristics such as maternal age, height, BMI, smoking status, depression status measured using the CES-D scale (18), employment, years of education and self-reported health (19)(20)(21)(22)(23)(24). At the household level we included household size, individual food security domains, per capita food expenditure below the Stats SA Poverty level of R274 and geotype (urban, rural or traditional areas) as well as province of residence.…”
Section: Covariatesmentioning
confidence: 99%
“…In the final review, articles were published from 10 countries among 46 countries were included. Of these studies, eleven studies were found from Ethiopia [13,19,[30][31][32][33][34][35][36][37][38], nine articles were from South Africa [20,22,[39][40][41][42][43][44][45][46], five articles were from Nigeria [18,[47][48][49][50], two studies were from Ghana [51,52], one article was from Kenya [53], three articles were from Tanzania [54][55][56], two studies were from Uganda [21,57] one study was from Burkina Faso [58], and one article was from Zambia [59]. Regarding the study designs, twenty-five (83%) of them were cross-sectional, three studies (3.5%) were cohort and three articles (3.5%) were case-control.…”
Section: Resultsmentioning
confidence: 99%
“…Variables associated with stunting and severe stunting were combined in a nal multiple logistic regression model. (17,18).…”
Section: Sample Characteristicsmentioning
confidence: 99%